Comparison of neonatal red cell transfusion reporting in neonatal intensive care units with blood product issue data: a validation study - Jillian A. Patterson; Jennifer R. Bowen; Sally Francis; Jane B. Ford (BMC, 2018)
Abstract Background Infants in Neonatal Intensive Care Units represent a heavily transfused population, and are the focus of much research interest. Such research commonly relies on custom research databases or routinely collected data. Knowledge of the accuracy of transfusion recording in these databases is important. This study aims to assess the reporting of red blood cell transfusion neonatal intensive care unit data compared with routinely collected hospital blood bank ("Blood Watch") data. Methods Blood Watch data was linked with the NICUS Data Collection, and with routinely collected birth and hospital data for births between 2007 and 2010. The sensitivity, specificity, and positive and negative predictive values for transfusion were calculated, compared to the Blood Watch data. The agreement between the NICUS and Blood Watch datasets on quantity transfused was also assessed. Results Data was available on 3934 infants, of which 16.2% were transfused. Transfusion was reported in the NICUS Data Collection with high specificity (98.3%, 95% confidence interval (97.8%,98.7%)), but with some under-enumeration (sensitivity 89.2% (95% CI 86.5%,91.5%)). There was excellent agreement between the NICUS and Blood Watch datasets on quantity transfused (Kappa 0.90, 95% CI (0.88,0.92)). Transfusion reporting in the hospital data for these infants was also reliably reported (Sensitivity 83.7% (95% CI 80.6%,86.5%), specificity 99.1% (95% CI 98.7%,99.4%)). Conclusions Transfusion is reliably reported in the neonatal intensive care unit data, with some under-reporting, and quantity transfused is well recorded. The NICUS Data Collection provides useful information on blood transfusions, including quantity of blood transfused in a high risk population.